Repeated reduction in parasite diversity in invasive populations of Xenopus laevis: a global experiment in enemy release - (:unkn) unknown (My University, 2019)
The introduction of species to multiple continents creates natural experiments suited to the evaluation of ecological hypotheses. For the Enemy Release Hypothesis (ERH), which postulates that the success of invasive populations hinges upon release from the effects of their natural enemies, assessments of parasite loss during invasion across independent geographical replicates are scarce. This study is the first to test the ERH for a globally invasive amphibian, Xenopus laevis, a successful invader on four conti- nents with a well-described parasite fauna. In this study, the metazoan parasite communities of X. laevis from 20 invasive and 27 native sites in five countries and three continents were compared. An overall pattern of reduced parasite diversity in invasive X. laevis was not yet countered by acquisition of novel parasites. Invasive X. laevis harboured impoverished parasite communities that were distinct from those of native X. laevis from undisturbed habitats. Con- versely, parasite communities from native X. laevis from disturbed habitats were similar to those from the invasive range. Accompanying parasites were com- mon in the native range and included both generalists with indirect and specialists with direct life cycles. Our findings emphasise that parasite loss is character- istic of the invasion process of X. laevis and possibly contributes to its success as a global invader. The ERH is supported in terms of metazoan parasites as natural enemies, irrespective of the geographical origin, climatic conditions and invasion history of the host populations. This study also draws attention to para- sites that co-invade with their hosts as invaders in their own right.
Keywords: African Research